Evolutionary Diversification of Primary Metabolism and Its Contribution to Plant Chemical Diversity - Maeda, Hiroshi A. (Frontiers in Plant Science, 2019)
Plants produce a diverse array of lineage-specific specialized (secondary) metabolites, which are synthesized from primary metabolites. Plant specialized metabolites play crucial roles in plant adaptation as well as in human nutrition and medicine. Unlike well-documented diversification of plant specialized metabolic enzymes, primary metabolism that provides essential compounds for cellular homeostasis is under strong selection pressure and generally assumed to be conserved across the plant kingdom. Yet, some alterations in primary metabolic pathways have been reported in plants. The biosynthetic pathways of certain amino acids and lipids have been altered in specific plant lineages. Also, two alternative pathways exist in plants for synthesizing primary precursors of the two major classes of plant specialized metabolites, terpenoids and phenylpropanoids. Such primary metabolic diversities likely underlie major evolutionary changes in plant metabolism and chemical diversity by acting as enabling or associated traits for the evolution of specialized metabolic pathways.